THE IDEA OF NIHILITY IN CONTEMPORARY IRAQI PAINTING - Zahraa mahood mohammad (Scholar Express Journal, 2023)
The study deals with the idea of nihility in contemporary Iraqi painting, and the methodological line was distributed between several axes, starting with the introduction, which contained the question of the problem and the importance of the study and its objectives and determining the terms, and then comes an explanation of the concept of nihility that accompanied the existence in contemporary thought. Nihility is no longer seen as the negative state that corresponds to the inevitable or natural verified existence, but rather as the basis for the renewal of individual and collective life patterns, which we find in the case of Sartre, Heidegger, Merleau-Ponte and Camy. The second axis dealt with cases of nihility in the styles of Iraqi artists that correspond to reality, as in impressionism and realism, and then nihility in abstract and postmodern non-formal styles. The study concludes with a set of results and conclusions that illustrate how to read the idea of nihility in the production of contemporary Iraqi art.
Keywords: production; introduction; contemporary; concludes